The environmental and economic impacts of the COVID-19 crisis on the Irish economy: An application of the I3E Model - Kelly C. De Bruin; Eoin Monaghan; Aykut Mert Yakut (The Economic and Social Research Institute (ESRI), 2020)
New research from the ESRI analyses how the COVID-19 crisis will impact upon the Irish economy and environment. It finds that Irish GDP is expected to decrease by around 13 per cent in 2020 as a result of the economic disruptions caused by the COVID-19 crisis. From an environmental perspective, economy-wide CO2 emissions are expected to decrease by 9.5 per cent this year. However, this reduction is short-lived as the low current energy prices increase energy demand and emissions rise again in 2021.
Keywords: 330; Coronavirus; Wirtschaftsprognose; Bruttoinlandsprodukt; Treibhausgas-Emissionen; Energieprognose; Irland